Rifaximin: An Option for the Treatment of Irritable Bowel Syndrome - Muhammad Abdul Quddus , Arslan Shahzad , Rukhsana Munawar , Khawaja Tahir Maqbool , Amna Mansoor , Naveed Gani , Sheikh Muhammad Taqqi Anwer (Journal of Islamic International Medical College, 2021)
Objective: To study the response of irritable bowel syndrome patients presenting with diarrhea and abdominal pain to the treatment with Rifaximin.